Guidance on Evaluation Terms of Reference (ToR) - CGIAR Independent Evaluation Arrangement (CGIAR Independent Evaluation Arrangement, 2015)
This guidance is intended to help evaluation managers to prepare ToRs that are comprehensive in their coverage, clear regarding the expectations from the evaluation and informative for the immediate users of the ToR.